Selective amino acid formulation enhances anion secretion and restores function in cystic fibrosis mutations - Grosche, Astrid; Sasidharan, Anusree; Salathe, Matthias; Baumlin, Nathalie; Angoli, Damiano; Prabhakaran, Sreekala; Xu, Xiaodong; Vidyasagar, Sadasivan (Frontiers in Pharmacology, 2025)
IntroductionIn cystic fibrosis (CF), most CFTR mutations cause partial (Class II) or complete (Class I) loss of function. Modulators (VX) can improve CFTR function in Class II mutations but are ineffective for Class I mutations and may cause side effects, resulting in tolerability issues with concerns about long-term safety. Apical anion secretion, essential for maintaining airway surface liquid (ASL) homeostasis, is regulated by CFTR. Alternative anion channels, like ANO1 and SLC26A9, also contribute to ASL homeostasis. Our recent work indicates that specific amino acids can modulate ion channel expression, activity, and trafficking in epithelial cells. We developed a select amino acid formulation (SAA) to enhance anion secretion in primary human bronchial epithelial cells (HBEC) with CF, regardless of mutation. MethodsTransepithelial short-circuit current was measured in wildtype (WT)- and CF-HBEC with various Class I and Class II mutations. Cells were pretreated with DMSO or VX for 24 h before apical exposure to SAA in Ussing chambers. Benzamil-insensitive current was sequentially inhibited to determine the contributions of SLC26A9, CFTR, ANO1, and NKCC1. 36Cl unidirectional and net fluxes (JnetCl) validated chloride secretion. Whole-cell patch-clamp studies determined the current density with SAA in WT- and CF-HBEC. CFTR, SLC26A9, and ANO1 mRNA and protein expression levels were assessed via qPCR and immunofluorescence. ASL volume, ciliary beat frequency (CBF), and mucociliary transport were also assessed.ResultsSAA increased benzamil-insensitive current to 70%–85% of WT cells, and enhanced JnetCl in both Class I and II mutations. JnetCl contributed to 72%, 50%, and 39.5% of S9A13-inhibitable current in WT-, F508del+/+-, and G542X/R785X-HBEC, respectively. VX treatment increased current in Class II but did not affect Class I mutations. Increased chloride secretion with SAA was attributed to enhanced activity of SLC26A9 and partial CFTR restoration through elevated mRNA and membrane protein expression. SAA also increased ASL volume and CBF, confirming its effectiveness in Class I mutations.DiscussionSAA enhances chloride secretion through SLC26A9 and partial CFTR rescue in Class I and II mutations. These findings suggest SAA functions as a mutation-agnostic therapy to improve anion secretion and clinical symptoms, particularly in Class I mutations.